A Comprehensive Analysis of Electronic Government Blueprint for Implementation Towards the Actual E-Government Implementation - Raha, Othman (2005)
There is still lack of study in the area of e-government in Malaysia currently even though it is part of Vision 2020. Hence, more study is needed to provide accurate insight of e-government scenario in Malaysia. After the e-government initiative took off in year 1997, there are numerous negative reports with regard to the current status of the e-government initiative. This has raised concern about the status of e-government implementation; whether it failed or succeeds. This study will investigate and analyze the implementation blueprint document produced by MAMPU against the actual e-government implementation. It will find out how much the document has been followed based on the condition for success described in the document. Then, the study will also use Heeks’ e-government readiness factors to identify if there’s any missing critical elements from the blueprint document which may have impact to the e-government implementation. The study will be conducted as an evaluation study and the methodology process is based on Babbie’s research process with minor modifications to suit the research scope. The results of this study have indicated that there are some areas from the blueprint document that are not being followed thoroughly. Also, there are areas that need to be included into the blueprint document such as human and legislative infrastructures in order to ensure smooth e-government implementation. Based on the result and findings of this study, several recommendations have been proposed in order to overcome the current issues addressed in this paper.